2022
DOI: 10.1002/acm2.13550
|View full text |Cite
|
Sign up to set email alerts
|

Onboard cone‐beam CT‐based replan evaluation for head and neck proton therapy

Abstract: Quality assurance computed tomography (QACT) is the current clinical practice in proton therapy to evaluate the needs for replan. QACT could falsely indicate replan because of setup issues that would be solved on the treatment machine. Deforming the treatment planning CT (TPCT) to the pretreatment CBCT may eliminate this issue. We investigated the performance of replan evaluation based on deformed TPCT (TPCTdir) for proton head and neck (H&N) therapy. Methods and materials: Twenty-eight H&N datasets along with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In most cases, the anatomy depicted in these images closely resembles that of the pretreatment CBCT images. However, inherent setup uncertainties during the QACT scan can introduce some mismatches between the QACT and CBCT images 14 . To mitigate this, deformable registration (DIR) is employed to align the QACT with the CBCT, resulting in the creation of the deformed QACT (dQACT).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most cases, the anatomy depicted in these images closely resembles that of the pretreatment CBCT images. However, inherent setup uncertainties during the QACT scan can introduce some mismatches between the QACT and CBCT images 14 . To mitigate this, deformable registration (DIR) is employed to align the QACT with the CBCT, resulting in the creation of the deformed QACT (dQACT).…”
Section: Discussionmentioning
confidence: 99%
“…The reference images were acquired from the same‐day QACT scans. Then, QACT images were deformed to cCBCT to obtain deformed QACT (dQACT) 14 using the built‐in function of RayStation. We compared the dose distributions obtained by Monte Carlo calculation using dQACT and sCT images, cCBCT and vCT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, not all HNC patients require APT during IMPT and the dosimetric benefits found in this review may overestimate the general benefit of APT. While Deiter et al [25] found that 63 % of the HNC patients needed IMPT replanning, Stanforth et al [30] found that approximately 30 % of their HNC cohort were replanned during IMPT. In accordance with this review, they found that in most cases one plan adaptation was sufficient to restore target coverage, and in some cases two plan adaptations were necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the current proton on-board CBCT 35 requires approximately 35 and 60 seconds for full-fan and half-fan scans. InverseNet3D is currently implemented in the framework.…”
Section: Discussionmentioning
confidence: 99%